Answer:
Brainliest pls
Step-by-step explanation:
Simplifying
2x + -10 = 4x + 5
Reorder the terms:
-10 + 2x = 4x + 5
Reorder the terms:
-10 + 2x = 5 + 4x
Solving
-10 + 2x = 5 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
-10 + 2x + -4x = 5 + 4x + -4x
Combine like terms: 2x + -4x = -2x
-10 + -2x = 5 + 4x + -4x
Combine like terms: 4x + -4x = 0
-10 + -2x = 5 + 0
-10 + -2x = 5
Add '10' to each side of the equation.
-10 + 10 + -2x = 5 + 10
Combine like terms: -10 + 10 = 0
0 + -2x = 5 + 10
-2x = 5 + 10
Combine like terms: 5 + 10 = 15
-2x = 15
Divide each side by '-2'.
x = -7.5
Simplifying
x = -7.5